Aneka Permasalahan Mengenai Perjanjian Kawin, Pengesahan atau Pencatatan - Sylvia Widjaja (Faculty of Law, Maranatha Christian University, 2015)
To make a prenuptial agreement is still considered as taboo by Indonesian couple, although there has been awareness to make such prenuptial agreement for transnational couple. Marriage in Indonesia is regulated under Law No. 1 of 1974 on Marriage (â€œMarriage Lawâ€). The prenuptial agreement is a term taken from the heading of the 5th Chapter of Marriage Law, which consist of only one article, i.e. article 29 paragraph 1, 2, 3 and 4, that only regulates the period of when the prenuptial agreement shall be made, itâ€™s legality, the time of when it will enter into force and the possibility to amend such agreement. In other words, Marriage Law does not describe the definition of prenuptial agreement, and also does not determine matters that can be agreed upon, which priorly regulated under the Indonesian Civil Code. In relation to the prenuptial agreement under the Marriage Law, there occur several legal questions, among others: First, Does the registration officer from the Civil Registration Office will only make registration of the prenuptial agreement or will he/she also legalizing it?. Second, Does the prenuptial agreement only regulate assets which originated from the grant and inheritance? And Last, Why the prenuptial agreement may only be made prior to the marriage, meanwhile the Marriage Law allows the amendment of the prenuptial agreement?. This research analyzes and discusses, and will provide answers or views to the above questions, which hopefully could be helpful and give insight for all readers.